MODEL ELASTISITAS PERMINTAAN ENERGI - Rahayu, Yuyun Puji (Universitas Negeri Yogyakarta, 2025)
Demand elasticity is used to measure individual responses to price changes. On a broader scale, the application of elasticity models and their development in measuring electricity fuel energy demand is often used. The question is whether the indicators, data and models used to measure this demand elasticity are the same in various countries or whether there are advantages or disadvantages of the selected model. This study examines the trend of the elasticity model of energy demand. Literature studies are used to provide explanations and descriptions of the results of recent studies related to changes in fuel and electricity prices in regions around the world. The results of the study show that the use of long-run data helps shape elasticity trends and assists a region in making policies or decisions. Elasticity research detects changes in consumer behaviour and set appropriate policies.